Environmental threats: perception, analysis and management - Brown Jennifer (ed.) (London, 1989)
Social Scientists are increasingly interested in the importance of identifying, measuring and managing environmental threats. Most books in this field have hitherto concentrated only on the perception of risk or the evaluation of specific hazards. The broader aim of this book is to provide an accessible and practical guide to current thinking in risk perception and management and presents an integrated and jargon-free overview, with contributions drawn from geography, psychology, policy studies, philosophy and anthropology. Emphasis is laid on reconciling social and technological factors, and expert solutions with public needs and wants. The roles of political attitudes, expert opinion, the media, and the public responses to technology are assessed, and their interplay examined. Overall, the book provides a stimulating and workable framework for the analysis of environmental threats that will be of importance not only for academic social scientists, but also for policy makers and planners in the environmental field and those interested in environmental politics.
Keywords: Environmental impact analysis